Small RNAs: An expanding world with therapeutic promises - Lan-Tao Gou; Qifan Zhu; Mo-Fang Liu (Fundamental Research, 2023)
Small non-coding RNAs (sncRNAs), such as microRNAs (miRNAs), small interfering RNAs (siRNAs), PIWI-interacting RNAs (piRNAs), and transfer RNA (tRNA)-derived small RNAs (tsRNAs), play essential roles in regulating various cellular and developmental processes. Over the past three decades, researchers have identified novel sncRNA species from various organisms. These molecules demonstrate dynamic expression and diverse functions, and they are subject to intricate regulation through RNA modifications in both healthy and diseased states. Notably, certain sncRNAs in gametes, particularly sperm, respond to environmental stimuli and facilitate epigenetic inheritance. Collectively, the in-depth understanding of sncRNA functions and mechanisms has accelerated the development of small RNA-based therapeutics. In this review, we present the recent advances in the field, including new sncRNA species and the regulatory influences of RNA modifications. We also discuss the current limitations and challenges associated with using small RNAs as either biomarkers or therapeutic drugs.